Application of the POE Learning Model to Improve Biology Learning Outcomes in Grade VII Students - Ferny M Tumbel; Verawati I. Y. Roring; Yustita Slamat (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This research explores using the Predict, Observe, and Explain (POE) model to enhance the learning process in elementary schools, particularly in biology lessons. The study conducted at SMP Berea Tondano with class VII focuses on how the POE model affects student understanding and engagement, specifically in classifying living organisms. A classroom action research (CAR) approach was employed in two cycles, each involving planning, action, observation, and reflection. Nine students from class VII participated in the study. Data were collected through observations, student activity sheets, and tests at the end of each cycle to evaluate the impact of the POE model on learning outcomes and student engagement. The research findings revealed significant improvements in student engagement and learning outcomes across the two cycles. In the first cycle, 55.56% of students achieved the learning goals, which increased to 88.89% in the second cycle. Similarly, student activity levels rose from 35.71% in the first cycle to 78.57% in the second cycle, reflecting greater participation and motivation. The study concludes that the POE model effectively enhances student learning outcomes and promotes active engagement. By involving students in prediction, observation, and explanation, the POE model aids in better understanding and retention of biological concepts. Further research is suggested to explore its application in other subjects and educational contexts.